Constipation in Children - Belkovsky, Mikhael; Santoro Angelo Zaragoza, Simone; Burgos Garcia, Carolyn; Abreu, Phillipe; Paiva Ortolan, Erika Veruska [UNESP]; Toledo de Arruda Lourenção, Pedro Luis [UNESP]; Bischoff, Andrea (Springer Nature, 2025)
Constipation in children has reported prevalence rates of up to 27% of the population [1, 2]. It is the principal complaint in 3% of all visits to pediatric outpatient clinics [3, 4]. The North American Society of Gastroenterology, Hepatology, and Nutrition (NASPGHAN) defines constipation as “a delay or difficulty in defecation, present for 2 weeks or more, and sufficient to cause significant distress to the patient” [3].